Phase Control of TiO2 Prepared by TiCl4 Hydrolysis and Electrochemical Method - Adrian Nur; Arif Jumari; Fauziatul Fajaroh; Nazriati Nazriati (Equilibrium Journal of Chemical Engineering, 2017)
The phase structure of  TiO2   dependent on  applications. It  is  importat to develop an effective method to control the phase structure of TiO2. In this study, the TiO2 was synthesized by TiCl4 hydrolysis method. The control of hydrolysis was done by electrochemical method  in  a  cell  consisting  of  two  plate  carbon  as  electrodes.  The electrodes distance was set to 2.6 to 4 cm and immersed in solution at dimensions of (5 ×2) cm. The electrodes were connected to the positive and negative terminals of a DC power supply for 1 to 2.5 hours. The voltage was varied from 5 to 15 V at constant stirring and room temperature. The resulted suspension was aged for 48 hours. The solution wasfiltered. The powder dried directly in an oven at 150°C for 2 hours, washed 2 times, and dried again 60 °C for 6 hours. In this work, the voltage, electrode distance, and TiCl4 initial concentration can control the phase structure of TiO2.